PENGARUH FASILITAS MOBILE BANKING DAN KUALITAS LAYANAN TERHADAP KEPUASAN NASABAH BANK SYARIAH DI PERUMAHAN BUMI PRESTASI KENCANA SAMARINDA - Mohd. Cahyo Situmorang; Norvadewi Norvadewi; Irma Yuliani (FEBI Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2022)
In this new normal era, people are increasingly aware of the importance of technology to facilitate transactions, especially during the Covid-19 virus era, considering that no one knows when the Covid-19 Virus will end. In the beginning, the residents of Bumi Kencana Residence became customers, many of whom came from mortgage financing (House Ownership Credit) and then continued as customers of Islamic Banks. banking and service quality on customer satisfaction of Islamic Banks. The purpose of this study was to determine the effect of Mobile-Banking Facilities on customer satisfaction of Islamic banks. Knowing the effect of Service Quality on customer satisfaction of Islamic banks, Knowing the effect of Mobile-Banking Facilities and service quality simultaneously on customer satisfaction of Islamic banks. research is quantitative research using primary data types. In this case, the researcher uses questionnaires to obtain data information. And secondary data In this case the researcher obtains secondary data from various references such as books related to research. the dependent variable used is customer satisfaction and the independent variable is mobile-banking facilities and service quality. The results showed that mobile-banking facilities and service quality had a significant effect on customer satisfaction using mobile-banking at Bumi Prestasi Kencana Housing Estate Samarinda. In the variable of mobile-banking facilities, namely tcount 2.619 > ttable 0.227, then H0 is rejected and Ha is accepted, meaning that the mobile-banking facility variable has a significant effect on customer satisfaction variables. on the service quality variable, namely tcount 4.245 > ttable 0.227, then H0 is rejected and Ha is accepted, meaning that the service quality variable has a significant effect on the customer satisfaction variable.